2004
DOI: 10.1021/mp034014y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Cell Penetrating Properties of RI-Tat-9:  Evidence for a Cell Type-Specific Barrier at the Plasma Membrane of Epithelial Cells

Abstract: Penetration of epithelial cells represents the rate-determining step for the absorption of many drugs and pharmaceutical macromolecules such as proteins and nucleic acid therapeutics. While the potential of using cell-penetrating peptides (CPPs) to facilitate absorption has been increasingly recognized, the mechanism of cell penetration and the uptake into certain cells have recently been called into question due to methodological artifacts. Therefore, the objective of this study was to quantitatively assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…Quantitative analysis of SecPen transfer from ten independent experiments indicates that, following the addition of 10 nmol of peptide in the basolateral compartment, 3.3 Ϯ 0.7 pmol of peptide are retrieved in the apical compartment after 1 h. In similar conditions, the transcytosis of transferrin is 50-fold less efficient. Previous studies on the passage of PTDs across epithelial monolayers have demonstrated that Tat and Penetratin PTDs are incapable of transcellular transport (13)(14)(15)(16) and, moreover, are poorly internalized by confluent MDCK cells (13,14,16). In agreement with these observations, we found that neither of these two peptides is transported across the epithelium in our system and that Penetratin internalization is significantly reduced when MDCK cells reach confluence (not shown).…”
Section: Discussionsupporting
confidence: 90%
“…Quantitative analysis of SecPen transfer from ten independent experiments indicates that, following the addition of 10 nmol of peptide in the basolateral compartment, 3.3 Ϯ 0.7 pmol of peptide are retrieved in the apical compartment after 1 h. In similar conditions, the transcytosis of transferrin is 50-fold less efficient. Previous studies on the passage of PTDs across epithelial monolayers have demonstrated that Tat and Penetratin PTDs are incapable of transcellular transport (13)(14)(15)(16) and, moreover, are poorly internalized by confluent MDCK cells (13,14,16). In agreement with these observations, we found that neither of these two peptides is transported across the epithelium in our system and that Penetratin internalization is significantly reduced when MDCK cells reach confluence (not shown).…”
Section: Discussionsupporting
confidence: 90%
“…In one of our previous studies to this subject, using linear human calcitonin derived CPPs, Tat (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) and penetratin (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), internalization into proliferating HeLa cells was superior to that in a fully polarized and differentiated MDCK model (7). Similarly, Zhang et al (24) suggested a cell type-specific barrier to control the internalization of RI-Tat-9 into HeLa, MT2, MDCK and Caco-2 cells.…”
Section: Discussionmentioning
confidence: 94%
“…Cell line dependence of CPP internalization has been suggested by different research groups (7,23,24). Previously, Hallbrink et al (34) hypothesized about a cell density dependent internalization of CPPs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…drug, fluorophore, nanoparticle, protein) and on cell type. 67 Moreover, uptake mechanism can be misassigned as a consequence of experimental artifacts, such as those resulting from cell fixation or omission of a proteolytic digestion. 68 In addition, some pharmacological agents used to probe specific mechanisms of endocytosis can interfere with multiple endocytic pathways as well as other cellular properties.…”
Section: Cell Penetrating Peptides: Background and Mechanism Of Uptakementioning
confidence: 99%